A consideration of the relations between Church and industry - Hulley, L D (Rhodes University, Faculty of Divinity, Department of Divinity, 1968)
[From Chapter 1]. The first point I wish to make, in fact it can be considered the primary one in this essay for what is to follow is a response to it, is that theology must be responding theology. This is a theology which takes the world seriously and responds to it in a Christian way. This is the approach we find in the New Testament: particularly in the Epistles, concrete problems and behaviour in the lives of his converts to which St. Paul responded prompted the didactic sections of his epistles. J. G. Davies supports this view in Planning for Mission "There are ... two primary realities'' he says "with which the congregation must be concerned: The Gospel of God and the world to which it is sent. 'Authentic theology' emerges out of the dialogue between the Gospel and the world." This is what Tillich calls the method of correlation. First we make an analysis of our situation and then try to relate the Christian message to the problems within it. While this compels us to rethink and reformulate many traditional Christian views, nothing "can change the substance of ... the ... answer, because this is the logos of being, manifest in Jesus as the Christ." This does not say that "we have all the answers" (in fact it will become clear that we do not), but it does express our conviction that the Christian Gospel has to do with life in all its aspects.
Keywords: Industries -- Religious aspects; Church and industry; Christian life